2014
DOI: 10.3109/09513590.2014.907262
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual function and childbearing potential after fertility-sparing surgery and platinum-based chemotherapy for malignant ovarian germ cell tumours

Abstract: Malignant ovarian germ cell tumours (MOGCT) account for 5% of all ovarian malignancies. Their elevated chemosensitivity, the frequent unilaterality and the young age of patients have strongly supported the conservative surgery as the standard approach, often followed by adjuvant platinum-based chemotherapy. The risk for recurrence is not affected by the performance of conservative versus radical surgery. During chemotherapy 50% of patients become amenorrhoeic but more than 95% of them resume normal menses afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…In previous studies, it was shown that FSS did not affect cancer prognosis in patients with MOGCT [ 30 34 ], but the pregnancy rate was not mentioned in most of them [ 29 ]. In this research, menstrual status, number of pregnancies and childbearing situation of the patients are studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was shown that FSS did not affect cancer prognosis in patients with MOGCT [ 30 34 ], but the pregnancy rate was not mentioned in most of them [ 29 ]. In this research, menstrual status, number of pregnancies and childbearing situation of the patients are studied.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies claimed that fertility-sparing surgery was the choice of treatment with ideal survival [ 11 , 17 , 33 , 34 , 36 38 ]. This research showed the preserving-fertility treatment may be the best management for young women with MOGCT to preserve fertility.…”
Section: Discussionmentioning
confidence: 99%
“…1 These tumours occur mainly in girls and young women, and the cure rate is relatively high as most cases exhibit excellent sensitivity to chemotherapy. Consequently, the extent of surgery is of vital importance to the quality of the patient's life.…”
Section: Introductionmentioning
confidence: 99%
“…There is concern regarding long-term toxicity of chemotherapy, but Kang et al showed that this regime did not impair ovarian function and fertility [33]. While women stopped menstruating during chemotherapy, over 85% have been shown to regain menstrual function once chemotherapy was completed [35][36][37]. These findings are reassuring that fertility can be preserved in women completing GCT treatment with successful pregnancies shown to match those of the general population [5].…”
Section: Treatment Of Gctmentioning
confidence: 99%